Common Fixed Point Theorems for Weakly (ψ,S,C)-Contractive Mappings in Partially Ordered b-Metric Spaces: Le Thi Chac, Nguyen Trung Hieu - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we introduce the notions of weakly (ψ,S,C)-contractive mappings and generalized weakly (ψ,S,C)-contractive mappings in partially ordered b-metric spaces and state some common fixed point theorems for these classes of mappings. These results generalize and improve the main results in [H.K. Nashine, Common fixed points via weakly (ψ, S, C)-contraction mappings on ordered metric spaces and application to integral equations, Thai J. Math. 12 (3) (2014) 729–747]. Also, some examples are given to illustrate the results.